The microbial fate of carbon in high-latitude seas: impact of the microbial loop on oceanic uptake of CO2 - Yager, Patricia L (My University, 1996)
This dissertation examines pelagic microbial processes in high-latitude seas, how they affect regional and global carbon cycling, and how they might respond to hypothesized changes in climate. Critical to these interests is the effect of cold temperature on bacterial activity. Also important is the extent to which marine biological processes in general impact the inorganic carbon cycle. The study area is the Northeast Water (NEW) Polynya, a seasonally-recurrent opening in the permanent ice situated over the northeastern Greenland continental shelf. This work was part of an international, multi-disciplinary research project studying carbon cycling in the coastal Arctic.The first chapter describes a simple model which links a complex marine food web to a simplified ocean and atmosphere. This model is designed to test the sensitivity of the air-sea flux of carbon to microbial food web structure and behavior, particularly those processes which might be sensitive to warming. Preliminary results suggest that organisms can impact short term air-sea carbon flux.The second chapter investigates the inorganic carbon inventory of the summertime NEW Polynya surface waters to establish the effect of biological processes on the air-sea pCO$\sb2$ gradient. A unique one-way sink for atmospheric carbon is hypothesized for the NEW Polynya and other seasonally-ice-covered seas. If this type of one-way carbon sink occurs on a global scale, it may provide a significant feedback to greenhouse warming.The third and fourth chapters use a kinetic approach to examine microbial activities in the NEW Polynya as a function of temperature and dissolved organic substrate concentration, testing the so-called "Pomeroy hypothesis" that microbial activity is disproportionately reduced at low environmental temperatures owing to increased organic substrate requirements. With field experiments, responsive microbial communities of mostly psychrophilic (cold-loving) organisms were often found to exhibit high affinities to and high incorporation efficiencies on nitrogen-rich organic matter; their response to temperature was heterogeneous, however, indicating that controls on microbial behavior may not be as simple as previously believed. Together, the suite of data collected on microbial activities, cell size, and grazing pressure suggest how unique survival strategies adopted by an active population of high-latitude bacteria may contribute to, rather than detract from, an efficient biological carbon pump.
Thesis (Ph. D.)--University of Washington, 1996
Keywords: Theses--Oceanography